The Observer's Sky Atlas With 50 Star Charts Covering the Entire Sky - Karkoschka, Erich. (Springer New York : Imprint: Springer, 2007)
The Observer's Sky Atlas contains star charts and information for all those who observe the night sky with unaided eyes, with binoculars, or with small telescopes, and also for those who just wish to look at constellations and interesting objects. Equally useful for the beginning observer and the old hand, the atlas presents: - A short introduction into observing the sky and a thorough description of the star charts and tables - Clearly arranged charts of all the stars (to 6th magnitude) visible with the unaided eye - Enlarged chart sections (to 9th magnitude) for binocular observation, highlighting 250 interesting nebulae, galaxies, and stellar clusters This new third edition features: - 32 additional pages with images of all the 250 nebulae covered in the atlas - An updated calendar for the next 20 years - Double star ephemerides from 2005-2020, including updated tables accompanying star charts - Predictions for dates and times of variable star minima/maxima based on recent observations The Observer's Sky Atlas is an indispensable and handy companion for every observer and has already appeared in four languages. Some praise for previous editions: "...The most informative little sky guide in the business." -Astronomy "The more experienced observer will find this slim volume useful at the telescope and...packed with interesting observing projects." -Sky & Telescope.